BRACU new campus development project construction schedule (01.07.22-31.07.22) - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the submission of construction schedule from 1 July, 2022 to 31 July, 2022 of BRACU new campus project.